VITAMIN D AND ASTHMA IN CHILDHOOD - Micevska, Vesna; Maretii, Tatjana Jakovska; Kirovski, Ilija; Jordanova, Olivera (Journal of Morphological Sciences, 2022)
Asthma is the most common chronic disease in children and one of the most common chronic disease in adults. It is defined as а chronic inflammatory disease of the airways, caused by the influence of many different cells and cellular elements (eosinophiles, mast cells and T-lymphocytes). The symptoms usually appear in childhood, and are associated with atopy and sometimes persist into adulthood. In the last decades, there has been an increased scientific interest in the research of vitamin D and its immunomodulatory effects, as well as the association of vitamin D deficiency and allergic disease development, especially asthma in childhood. The study was prospective and was performed at the Pulmonology Department at the University Children’s Hospital in Skopje on 120 oupatient children between the ages of 2-14 years. The  examined group consisted of 60 children with asthma, and the control group consisted of 60 healthy children. Serum levels of vitamin D was measured in both groups. The examined group was treated with inhaled corticosteroids, and the participants with vitamin D deficiency were also treated with oral vitamin D. The results from the pulmonary function testing for bronchial hyperreactivity and the episodes of bronchoobstructions after 6 months follow-up were compared to the one at the beginning of the asthma therapy. Mean serum vitamin D levels in the asthmatic children were 24.57 ± 10.0, and for the healthy children they were 28.74 ± 9.5, with a statistical significant difference of p=0,0021. 46,67% of the asthmatic children had vitamin D deficiency, versus 15% of the healthy children. In our study, vitamin D supplementation had no significant impact in asthma control efficacy. Children with asthma have lower serum levels of vitamin D, versus healthy individuals. Although vitamin D supplementation in asthmatic children hasn’t improved the asthma treatment efficacy, the data shows positive therapeutic effects in patients with more severe symptoms. Key words: asthma, vitamin D deficiency, children. https://doi.org/10.55302/JMS2251011m